Performance of Organic Polymer Electrolyte Based on Extracted Aloe Vera Polysaccharide Compared with Mannose, Agarose and Carboxymethyl-Cellulose (CMC) for DSCs Application - Yuharmon, N.A.S. (Springer Science and Business Media B.V., 2021)
In this work, the performance of integrated DSC based on AVG/CMC-rGO-Iâ/I3 â gel polymer electrolyte has been compared with the mannose/CMC-DMSO-rGO-Iâ/I3 â, agarose/CMC-DMSO-rGO-Iâ/I3 â and CMC/PEG-DMF-rGO-Iâ/I3 â gel polymer electrolyte. The gel polymer electrolyte were characterized using field-emission scanning electron microscopy (FESEM) in order to examine the cross-section images of the gel polymer electrolyte thickness, currentâvoltage (I-V) measurement and electrochemical impedance spectroscopy (EIS). The fabricated test cells with an active area of 0.40 cm2 incorporated with AVG/CMC-rGO-IË/I3Ë gel polymer electrolyte, possess the highest conversion efficiency (Î·) of 0.84. However, it still considered lower compared to mannose (2.35), agarose (3.55) and CMC (5.76) gel polymer electrolyte, due to the lower percentage of the extracted polysaccharides. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.